The bird remains from WF16, an early Neolithic settlement in southern Jordan: Assemblage composition, chronology and spatial distribution. (10th July 2021) - White, Judith; Finlayson, Bill; Makarewicz, Cheryl; Khoury, Fares; Greet, Ben; Mithen, Steven
Abstract: Excavations at the early Neolithic settlement of WF16 in Faynan, southern Jordan, 11.84–10.24 ka BP, recovered 17, 700 bird bones, of which 7808 could be identified to at least family level. Sixty‐three different bird taxa are present from 18 families, representing a mix of resident and migrant birds, based on present‐day ecology. We describe the settlement context for the assemblage, its taxonomic composition, spatial and chronological distribution, identifying its similarities and differences to avian assemblages from broadly contemporary sites in the region.